Seagrape (Caulerpa racemosa) Flour Combination with Wheat and Sago Affects Physical Characteristics of Dry Noodles - Tanod, Wendy; Melongkade, Regina Juliana; Maliode, Yunita Isabela; Ansar, Novalina Maya Sari; Cahyono, Eko; Rieuwpassa, Frets Jonas; Sambeka, Yana; If'all, If'all (Journal of Food and Culinary, 2024)
Dry noodles, commonly produced from wheat flour, have been associated with health issues, including obesity, when consumed in excess. Moreover, reliance on imported wheat flour requires local alternatives to enhance its acceptability within the community. This study aimed to evaluate the physical characteristics of dry noodles incorporating a blend of wheat flour, sago flour, and seagrape flour (Caulerpa racemosa). The study involved experimental treatment with varying amounts of added seagrape flour (0, 5, 10, 15, and 20 g). Additionally, the study evaluated the proximate composition of seagrape and sago flour was sourced from Sangihe Islands. The physical attributes analysed in the combined dry noodles included the moisture content, water absorption, cooking loss, and cooking time. Proximate analysis of seagrape flour revealed carbohydrate content of 47.83%, protein 19.78%, ash 17.83%, moisture 12.37%, and fat 2.19%. Sago flour had a proximate content of 87.45% carbohydrates, 11.7% moisture, 0.42% protein, 0.32% ash, and 0.11% fat. The moisture content of the combined dry noodles ranged from 6.83 to 7.83%, water absorption from 72.73 to 90.27%, cooking loss from 8.23 to 13.27%, and cooking time from 7.00 to 7.09 minutes. In conclusion, seagrape flour in the formulation influenced the water absorption and cooking loss of dry noodles prepared from wheat and sago flours. However, the combined dry noodles had no significant impact on the moisture content and cooking time.